1989
DOI: 10.1007/bf01892896
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulating therapy of rheumatoid arthritis by high-dose intravenous immunoglobulin

Abstract: 11 patients with rheumatoid arthritis were treated with intravenous immunoglobulin (IVGG). In 6 patients clinical results were impressive, although lasting responses could be achieved in 3 patients only. This treatment was immunomodulating, since the immunoregulatory T-cell ratio (CD4/CD8) decreased following therapy by reducing CD4-positive cells in-vivo. By use of anti-mu-antibodies as a B-cell specific mitogen, IVGG-treatment was seen to suppress early processes of B cell activation. In parallel to these ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Case reports, open-label trials, and controlled studies of high-dose IVIG have shown some benefit in patients with rheumatoid arthritis (RA). [204][205][206][207][208][209] In contrast, low-dose (5 mg/kg every 3 weeks) therapy in a randomized, double-blind, placebo-controlled trial in 20 patients with refractory RA demonstrated no benefit. 210 Juvenile idiopathic arthritis.…”
Section: Rheumatic Diseasesmentioning
confidence: 99%
“…Case reports, open-label trials, and controlled studies of high-dose IVIG have shown some benefit in patients with rheumatoid arthritis (RA). [204][205][206][207][208][209] In contrast, low-dose (5 mg/kg every 3 weeks) therapy in a randomized, double-blind, placebo-controlled trial in 20 patients with refractory RA demonstrated no benefit. 210 Juvenile idiopathic arthritis.…”
Section: Rheumatic Diseasesmentioning
confidence: 99%
“…Non-specific immunoglobulins such as polyclonal IgG or IgM may also dissociate antigen-antibody complexes or inhibit their formation [8,[20][21][22]. In addition, large doses of non-immune IgG given intravenously may decrease the amount of circulating immune complexes [23,24], suppress auto-antibody production [25,26], and alter the proportions of T-cell populations [27] in some autoimmune diseases. These effects are commonly attributed to mechanisms mediated by specific antibodies which are assumed to be present in the preparations [25,28].…”
Section: Introductionmentioning
confidence: 99%